Observation of Postpartum Complications and Neonatal Birthweight among 54 cases of Cesarean Section - Shaheen Ferdous (SSB Global Journal of Medical Science, 2024)
Background: The puerperal period is critical for both the physical and emotional well-being of the mother and newborn. Cesarean sections are associated with various postpartum complications and neonatal outcomes, which necessitate thorough observation and management. Objective: To observe the puerperal conditions and neonatal birth weights among women who underwent cesarean sections at Enam Medical College Hospital, Dhaka, Bangladesh. Methods: This cross-sectional observational study was conducted at Department of Gynae and Obs, Pabna Medical College, Pabna, Bangladesh during the period from June 2014 to December 2014. A total of 54 patients who had given birth via cesarean section were included. Data on age, pregnancy duration, clinical complaints, comorbidities, previous cesarean section history, puerperal complications, and neonatal birth weights were collected and analyzed. Results: The majority of participants were aged 21-30 years (66.67%), with a mean age of 26.50 years. Most pregnancies lasted more than 37 weeks (46.30%). Clinical complaints included lower abdominal pain (40.74%) and per vaginal discharge (20.37%). Comorbidities such as gestational diabetes (25.93%) and anemia (24.07%) were prevalent. Previous cesarean section history showed that 57.41% had no prior cesarean sections, 25.93% had one, and 16.67% had two previous cesarean sections. Puerperal complications included tenderness (66.67%) and excessive bleeding (16.67%). Neonatal birth weights were classified as low birth weight (37.04%), normal birth weight (59.26%), and overweight (3.70%), with a mean birth weight of 2.749 kg (SD ± 0.497 kg). Conclusion: The study highlights the significant prevalence of clinical complaints, comorbidities, and puerperal complications among women undergoing cesarean sections. These findings emphasize the need for comprehensive monitoring and targeted interventions to reduce maternal and neonatal morbidity, particularly in low-resource settings.